2015
DOI: 10.1093/ofid/ofv051
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic Body Washes for Reducing the Transmission of Methicillin-Resistant Staphylococcus aureus: A Cluster Crossover Study

Abstract: In a cluster cross-over trial, targeted decolonization with octenidine body washes was not associated with reduction in MRSA transmission or infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…T he rise in bacterial infections that are resistant to one or more frontline antibiotics has led to a greater reliance on prevention through effective infection control practices (IPCs). This is essential for reducing the burden of nosocomial infections and includes the use of antiseptics and disinfectants-e.g., the use of body washes to help reduce nosocomial infections in high-risk areas such as intensive care units (ICUs) (1,2). The antiseptic octenidine has showed promising efficacy against a wide variety of multidrug-resistant (MDR) pathogens (3,4), as well as reducing the rate of infection with Gram-negative agents through daily body washing (5).…”
mentioning
confidence: 99%
“…T he rise in bacterial infections that are resistant to one or more frontline antibiotics has led to a greater reliance on prevention through effective infection control practices (IPCs). This is essential for reducing the burden of nosocomial infections and includes the use of antiseptics and disinfectants-e.g., the use of body washes to help reduce nosocomial infections in high-risk areas such as intensive care units (ICUs) (1,2). The antiseptic octenidine has showed promising efficacy against a wide variety of multidrug-resistant (MDR) pathogens (3,4), as well as reducing the rate of infection with Gram-negative agents through daily body washing (5).…”
mentioning
confidence: 99%
“…There was moderate evidence of benefit from one ITS, 104 one controlled trial 148 and one CBA study 101 which investigated the effectiveness of skin decolonisation with octenidine on the incidence of MRSA acquisition and the incidence of MRSA infection. The results of the metaanalyses showed that octenidine alone or in combination with a nasal decolonisation agent was more effective when compared to no decolonisation or placebo.…”
Section: Octenidinementioning
confidence: 99%
“…There was moderate evidence from two studies 101,148 which reported adverse events associated with the use of octenidine. One study which assessed adverse events when using octenidine soap reported no events in a sample of 5277 patients 148 while another assessing octenidine nasal gel reported one case (1/731, 0.14%) of adverse events (not specified) which resulted in discontinuation of use of the nasal gel in the affected patient. 101 No evidence was found from the studies published since 2004 meeting the inclusion criteria for the study design, which assessed the cost-effectiveness of octenidine.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…As observed from previous studies, antiseptic bathing alone is inadequate for reducing MRSA acquisition in acute-care hospitals. 10 Although the nares are the most frequently colonized anatomic site and a major reservoir for MRSA, decolonization strategies commonly include universal antiseptic bathing but not nasal decolonization. With the wider availability of intranasal antiseptics, the inclusion of nasal decolonization in strategies to reduce nosocomial transmission of MRSA can be safely administered without the need for concern of mupirocin resistance.…”
Section: Discussionmentioning
confidence: 99%